Application of information technology (IT) in the management of court records in the supreme court of Nigeria (2005)
Information technology (IT) being crucial to the management of records in all sectors, the study investigated the level of awareness and application of IT to court records management in the Supreme Court of Nigeria. It examined the facilities available, use, constraints and prospects. The research instruments adopted for data collection were interview and observation. The results showed that there is high level of awareness of the importance of IT. The technology is used mainly for record creation and distribution. Constraints include poor funding and lack of well-trained staff in the use of IT for records management. The study concluded and made necessary recommendations for the improved use of IT for court record management in the Supreme Court of Nigeria.